2020
DOI: 10.1083/jcb.201908164
|View full text |Cite
|
Sign up to set email alerts
|

Citrullination regulates wound responses and tissue regeneration in zebrafish

Abstract: Calcium is an important early signal in wound healing, yet how these early signals promote regeneration remains unclear. Peptidylarginine deiminases (PADs), a family of calcium-dependent enzymes, catalyze citrullination, a post-translational modification that alters protein function and has been implicated in autoimmune diseases. We generated a mutation in the single zebrafish ancestral pad gene, padi2, that results in a loss of detectable calcium-dependent citrullination. The mutants exhibit impaired resoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In the course of vertebrate evolution, citrullination was thus expanded in scope and adapted to a variety of cellular contexts, ranging from neutrophil extracellular trap release to stem cell potency, and from oligodendrocytes to bone marrow and keratinocytes ( Nicholas and Bhattacharya 2014 ). The emerging physiological roles of the vertebrate PADIs, such as in the regulation of pluripotency and embryonic development ( Brahmajosyula and Miyake 2013 ; Christophorou et al 2014 ; Xu et al 2016 ; Xiao et al 2017 ), and the newly described role of the fish PADI in tissue regeneration ( Golenberg et al 2020 ), point to possible selective advantages conferred to metazoans by PADIs and offer a possible explanation for the fact that PADIs were retained so widely ( Huang 2013 ). In a similar vein, it is interesting to consider our findings in light of the proposal that genes with a role in antimicrobial defence are amenable to co-option by eukaryotic innate immune systems ( Chou et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the course of vertebrate evolution, citrullination was thus expanded in scope and adapted to a variety of cellular contexts, ranging from neutrophil extracellular trap release to stem cell potency, and from oligodendrocytes to bone marrow and keratinocytes ( Nicholas and Bhattacharya 2014 ). The emerging physiological roles of the vertebrate PADIs, such as in the regulation of pluripotency and embryonic development ( Brahmajosyula and Miyake 2013 ; Christophorou et al 2014 ; Xu et al 2016 ; Xiao et al 2017 ), and the newly described role of the fish PADI in tissue regeneration ( Golenberg et al 2020 ), point to possible selective advantages conferred to metazoans by PADIs and offer a possible explanation for the fact that PADIs were retained so widely ( Huang 2013 ). In a similar vein, it is interesting to consider our findings in light of the proposal that genes with a role in antimicrobial defence are amenable to co-option by eukaryotic innate immune systems ( Chou et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…A notable insight into this question is offered by a recent study in fish. Golenberg et al deleted the single PADI in zebrafish and found that this protein regulates wound healing and fin regeneration [171]. It is not yet known how the PADI-null zebrafish respond to infection and it is possible that PADIs have acquired different roles, even throughout animal evolution.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Using double transgenic zebrafish to simultaneously image neutrophils and macrophages has become standard practice for determining their unique contributions and interactions during wound healing and cancer. [52][53][54][55] While there has been substantial focus on neutrophil and macrophage migration and function, transgenic zebrafish lines exist for the visualization of other leukocyte populations. The Lck promoter has been used to label and visualize bulk T cell populations in vivo, 56,57 and fluorescent expression under the CD4.1 or Foxp3 promoters allows for the visualization of helper or regulatory T cell subsets, respectively.…”
Section: Advan Ce S In the Tool S Us Ed For Imag Ing Infl Ammati On I...mentioning
confidence: 99%
“…The mpeg1 and mfap4 promoters specifically label macrophages but not neutrophils in the zebrafish system 50,51 . Using double transgenic zebrafish to simultaneously image neutrophils and macrophages has become standard practice for determining their unique contributions and interactions during wound healing and cancer 52‐55 . While there has been substantial focus on neutrophil and macrophage migration and function, transgenic zebrafish lines exist for the visualization of other leukocyte populations.…”
Section: Advances In the Tools Used For Imaging Inflammation In Zebra...mentioning
confidence: 99%